Parasitic Nematodes of Plant Persimmon (Diospyros Kaki, l.) Rhizosphere in District Swat, Kp Pakistan - Nadia Saeed, Seema Anar, Qasim Saeed, Khalid Usman, Javed Ahmed Ujjan, Fahim Haider Jamali, Iftikhar Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Different species of plant parasitic nematodes of persimmon (Diospyros kaki, L.) were identified from various localities of District Swat KPK Pakistan namely Chail, Madyan, Piya, Jare, Chikrai, Thesil, Fateh pur, Baghdheri, Naway kalay, Shin, Pirpatay, Sambat and Gurra. Methods: Soil samples were collected from the bases of persimmon trees along with rhizospheres that show stunted growth. The collected samples were then processed by using modified Bearmann funnel technique. Nematode specimens isolated in cavity block were killed by heat and treated with TAF (Triethylamine formaldehyde) solution. Findings and Practical implication: After 24 hours, the specimens were transferred to 1.25 % glycerin with trace amount of picric acid for staining of nematodes. Nine different species of nematodes were reported from these localities were Tylenchus spp, Psilenchus spp, Meloidogyne larvae, Aphelenchus spp, Tylenchus juveniles, Filenchus spp, Pratylenchus spp, Helicotylenchus pseudorobustus and Helicotylenchus dihystera. Helicotylenchus species were more common in the collected samples. Conclusion: It is concluded from analysis of soil samples that plant parasitic nematodes associated with persimmon cause economic loss in district swat. Persimmon plants show stunted and retarded growth in soil which has high nematode population density. Keywords: Nematodes, Persimmon, Swat, Diospyros kaki, Triethylamine formaldehyde.